The dynamics of hypertension and renal function in CKD and non-CKD patients affected with COVID-19 – final results of BIRCOV trial - Ivanov, Dmytro; Gozhenko, Antolii; Ivanova, Mariia; Zavalna, Iryna; Crestanello, Tommy (European Journal of Clinical and Experimental Medicine, 2023)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. There is evidence in the literature about a change in the effectiveness of inhibitors of the renin-angiotensin system (iRAS) in people with COVID-19. Considering different mechanisms of pressure reduction by different iRAS groups, one can expect differences in people with COVID-19 receiving these drugs. The aim of angiotensin-converting enzyme inhibitors (ACEi), angiotensin II receptor blockers (ARB) and direct renin inhibitors (DRi) usage in COVID-19 (BIRCOV study) was to pinpoint clinical and laboratory differences in people with hypertension who received iRAS and suffered coronavirus infection. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. An open prospective trial of 108 patients was performed in subjects suffering from COVID-19 who have been receiving iRAS: ACEi, ARB or DRi as basic antihypertensive therapy. The disease follow-up was 12 and 24 weeks. A blood pressure (BP) measurement was performed the week before COVID-19 and up to 24 weeks from the disease onset. Subanalysis in patients with chronic kidney disease (CKD) was performed. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. In patients with COVID-19, a change in the effectiveness of antihypertensive therapy depending on the type of drug in the iRAS group has been documented in the first 4 weeks from the onset of the disease. The use of ACEi had significantly increased the risk of severe hypotension, unlike ARBs that do not cause hypotension. The synchronous decline of estimated glomerular filtration rate (eGFR) and systolic BP was more pronounced in CKD patients followed by albuminuria incidence. The greatest decrease in eGFR was in people taking ACEi. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. People with grade 1-2 hypertension who are constantly receiving RAS inhibitors suffering from COVID-19 may develop hypotension with ACEi. COVID-19 leads to transient albuminuria and decreased glomerular filtration rate, which is especially dangerous for people with CKD 4-5.